An oversaturated silver bismuth solid solution nanoparticle, a preparation method thereof and application thereof in sintering slurry
Patent Information
- Application Number
- CN202410921027.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-07-10
- Publication Date
- 2026-10-09
- Estimated Expiration
- 2044-07-10
AI Technical Summary
[0005]本发明针对现有纳米浆料中烧结温度高的问题,提供一种超饱和银铋固溶体纳米颗粒及其制备方法和在烧结浆料中的应用
[0030] This invention employs a low-temperature in-situ chemical synthesis method. By selecting a suitable solvent, the solubility and concentration of silver and bismuth metal salts are simultaneously increased. A strong reducing agent is used to achieve a rapid, unsteady-state reaction in the liquid phase, simultaneously and in situ reducing the two metal ions (silver and bismuth). This allows the metals to rapidly nucleate and grow in the liquid phase. Under the influence of the unsteady-state reaction mechanism, bismuth atoms are neatly arranged in the face-centered cubic lattice of silver, forming an unsteady but stable silver-bismuth binary single-phase supersaturated solid solution. The bismuth content in this solution far exceeds that in thermodynamically stable silver-bismuth solid solution alloys, and it exists stably within nanoparticles, forming a single-phase solid solution with an average particle size of 5 nm to 500 nm. Although this solid solution is supersaturated at room temperature in a macroscopic state, it can exist stably for a long time at the nanoscale.
Smart Images

Figure CN118875307B_ABST
Abstract
Description
Technical Field
[0001] This invention relates to a supersaturated silver-bismuth solid solution nanoparticle, its preparation method, and its application in sintering slurry, belonging to the field of sintering materials and their preparation technology. Background Technology
[0002] With the increasing application of third-generation semiconductors, led by gallium nitride (GaN) and silicon carbide (SiC), in power devices such as radio frequency devices, power devices, high-power LED devices, insulated-gate bipolar transistors (IGBTs), and laser modules, the high breakdown voltage and wide bandgap characteristics of third-generation semiconductors determine the high voltage withstand capability of these power devices. Furthermore, their high thermal conductivity and high heat resistance allow them to withstand higher junction temperatures. In addition, power devices, primarily used in automotive electronics, high-voltage power transmission, and charging equipment, operate in harsh environments, typically requiring high temperatures and direct sunlight. These characteristics dictate that the service temperature of third-generation semiconductor devices is significantly higher than that of traditional silicon-based power devices, often exceeding 200°C, and sometimes even reaching peak temperatures of 600°C. This places extremely stringent requirements on the heat resistance and heat dissipation of the device package. Currently, solder joints in packages commonly use tin-based solder as the connection material, but excessively high service temperatures can cause rapid solder joint degradation, and occasionally even exceed the melting point of the solder, leading to device failure.
[0003] Existing research indicates that nano-silver-based nano-slurries are undoubtedly the best alternative to traditional solders. These materials can be sintered at low temperatures and their thermal conductivity can be 3-4 times that of traditional tin-based solders. However, the sintering temperature of nano-silver pastes is difficult to lower than 200℃, while the rapidly developing nano-copper pastes even require sintering above 250℃. Applications of nano-slurries often require even lower sintering temperatures. For example, higher sintering temperatures can lead to higher internal thermal stress in the solder joints, affecting their reliability. Some devices require gradient interconnects, thus necessitating sintering materials below 200℃. Furthermore, besides power devices, some devices with poor heat resistance require high thermal conductivity in their packages; the sintering temperatures of nano-silver and copper limit their applications in these areas. For single-metal nano-slurries, it is difficult to further reduce the sintering temperature through processing methods, and nanoscale low-melting-point metals are generally prone to oxidation, have poor storage performance, and are difficult to sinter.
[0004] In recent years, based on single-unit nano-metal pastes, researchers have developed a few nano-pastes with binary or even multi-unit alloy nanoparticles as solid phase components. These include different types of multi-unit alloys such as copper-silver, copper-tin, and silver-aluminum. Among these, copper-silver alloys have been studied the most, including copper-silver core-shell nanoparticles and copper-silver solid solution nanoparticles. The main advantages of these materials include resistance to electromigration, corrosion resistance, and low cost. However, due to the high melting point of copper, the sintering temperature is higher than that of nano-silver. In addition, copper-tin compound alloy nanoparticles also have the problem of high sintering temperature. Therefore, in order to reduce the sintering temperature, it is necessary to add low-melting-point metals to nano-silver to meet the requirements of sintering at 180°C or even lower. Summary of the Invention
[0005] This invention addresses the problem of high sintering temperatures in existing nano-slurries by providing a supersaturated silver-bismuth solid solution nanoparticle, its preparation method, and its application in sintering slurries.
[0006] The technical solution of the present invention:
[0007] One objective of this invention is to provide a method for preparing supersaturated silver-bismuth solid solution nanoparticles, the method comprising the following steps:
[0008] (1) Silver metal salt and bismuth metal salt are placed in a reaction vessel in proportion, organic dispersant and solvent are added, and the mixture is stirred until completely dissolved to obtain a precursor solution;
[0009] (2) The precursor solution and the reducing agent solution were mixed and reacted under low temperature conditions to obtain silver bismuth solid solution nanoparticles.
[0010] Further specifying, (1) the silver metal salt is one or more of silver nitrate, silver sulfate, silver oxalate, silver chloride, silver bromide, and silver iodide.
[0011] Further specifying, (1) the bismuth metal salt is one or more of bismuth nitrate, bismuth chloride, bismuth nitrate, and bismuth oxide.
[0012] Further specifying, the organic dispersant in (1) is one or a mixture of citric acid, sodium citrate, polyvinylpyrrolidone, octadecylamine, hexadecyltrimethylammonium bromide, sodium dodecylbenzenesulfonate and dodecyl mercaptan.
[0013] Further specifying, the solvent in (1) is one or more of ethanol, acetone, ethylene glycol, ethyl acetate, dichloromethane, methyl chloride, dimethylformamide, ethylene glycol ether, 1,2-ethylene glycol, and ethylene glycol butyl ether, or is water and one or more of ethanol, acetone, ethylene glycol, ethyl acetate, dichloromethane, methyl chloride, dimethylformamide, ethylene glycol ether, 1,2-ethylene glycol, and ethylene glycol butyl ether.
[0014] Further specified, the total concentration of silver and bismuth metal salts in the precursor solution of (1) is 0.01 to 10 mol / L.
[0015] Furthermore, the molar content of bismuth salt in the precursor solution is 0.0001 to 30% of the total molar content of metal salt.
[0016] Further specified, the concentration of organic dispersant in the precursor solution of (1) is 0.1 to 10 g / L.
[0017] Further specifying, the reducing agent in (2) is one or more of the following: hydrazine hydrate, sodium borohydride, potassium borohydride, sodium hypophosphite, polyol, and ascorbic acid.
[0018] Further, the concentration of the reducing agent in the reducing agent solution of (2) is 0.1 to 10 mol / L.
[0019] Further specifying, the total molar ratio of the reducing agent and the metal salt in the precursor solution added in (2) is (1-5):1.
[0020] Further specified, (2) under medium and low temperature conditions, the reaction temperature is -50 to 50℃, the time is 2 to 60 min, and the stirring speed is 200 to 2000 r / min.
[0021] Further specifying, (2) the mixing method of the precursor solution and the reducing agent solution includes adding the reducing solution dropwise into the precursor solution, or pouring the reducing solution directly into the precursor solution.
[0022] Furthermore, the dropping rate of the reducing solution into the precursor solution is specified to be 0.01–5 mL / s.
[0023] The second objective of this invention is to provide a supersaturated silver-bismuth solid solution nanoparticle prepared by the above method, specifically wherein the molar content of bismuth element in the nanoparticle is 0.0001-30%, and the particle size is 5-500 nm.
[0024] The third objective of this invention is to provide a sintering slurry, specifically, the sintering slurry is composed of supersaturated silver-bismuth solid solution nanoparticles prepared by the above method, an organic solution, a dispersant, a flux, and a binder in a mass percentage ratio of 50-90%: 5-45%: 0.01-5%: 0.01-5%: 0.01-5%, and the solid content of the sintering slurry is above 80%.
[0025] Further specifying, the organic solution is one or a mixture of ethanol, ethylene glycol, diethylene glycol, triethylene glycol, terpineol, polyethylene glycol, glycerol, and ethyl acetate.
[0026] Further specifying, the dispersant is one or a mixture of citric acid, sodium citrate, β-cyclodextrin, octadecylamine, hexadecyltrimethylammonium bromide, sodium dodecylbenzenesulfonate, and dodecyl mercaptan.
[0027] Further specifying, the flux is rosin resin or a rosin resin derivative; the binder is one or more of stearic acid, fish oil, polyethylene terephthalate, and epoxy resin.
[0028] The fourth objective of this invention is to provide a low-temperature sintering method for the above-mentioned sintering paste, wherein the method comprises: screen printing the sintering paste onto the substrate pads, aligning and placing the chip, hot-pressing and sintering at a temperature above 180°C, and sintering for 5 to 200 minutes under a sintering pressure of 0 to 30 MPa.
[0029] Beneficial effects:
[0030] This invention employs a low-temperature in-situ chemical synthesis method. By selecting a suitable solvent, the solubility and concentration of silver and bismuth metal salts are simultaneously increased. A strong reducing agent is used to achieve a rapid, unsteady-state reaction in the liquid phase, simultaneously and in situ reducing the two metal ions (silver and bismuth). This allows the metals to rapidly nucleate and grow in the liquid phase. Under the influence of the unsteady-state reaction mechanism, bismuth atoms are neatly arranged in the face-centered cubic lattice of silver, forming an unsteady but stable silver-bismuth binary single-phase supersaturated solid solution. The bismuth content in this solution far exceeds that in thermodynamically stable silver-bismuth solid solution alloys, and it exists stably within nanoparticles, forming a single-phase solid solution with an average particle size of 5 nm to 500 nm. Although this solid solution is supersaturated at room temperature in a macroscopic state, it can exist stably for a long time at the nanoscale.
[0031] The solid solution was further prepared into a nano-slurry. This nano-slurry relies on a high silver content to ensure the thermal and electrical conductivity of the solder joints. The doping with low-melting-point bismuth can lower the sintering temperature of the slurry, allowing sintering at ultra-low temperatures of 180°C or even lower. Furthermore, the sintering process is less demanding, allowing for sintering in air. This effectively mitigates the electromigration effect of the solder joints and reduces the cost of the slurry. Through a specified sintering process, high thermal conductivity, high strength, and high reliability encapsulated solder joints are finally obtained. Experimental results show that the shear strength of the sintered solder joints is 12–40 MPa, and the thermal conductivity is 100–300 W / (m·K).
[0032] In addition, after sintering, bismuth precipitates at the grain boundaries of the nano-slurry to achieve grain boundary strengthening. The introduction of bismuth effectively prevents the electromigration and electrochemical migration effects of silver, thus significantly improving the reliability of power devices.
[0033] In summary, the nano-slurry provided by this invention can meet the requirements of power devices with poor heat resistance that require low-temperature sintering, and also meet their high thermal conductivity requirements. It can be used for interconnection of 3D multi-dimensional packaged devices with gradient interconnection. The low sintering temperature saves energy and process costs, and the low residual thermal stress inside the solder joint allows it to be adapted to thinner solder joint processes without the need for high-thickness solder joints to relieve thermal stress, further reducing process costs. In addition, it can also be matched with the process window of existing tin-based production lines. Attached Figure Description
[0034] Figure 1 TEM images (at different magnifications) of the supersaturated silver-bismuth alloy nanoparticles prepared in Example 1;
[0035] Figure 2 The XRD pattern of the supersaturated silver-bismuth alloy nanoparticles prepared in Example 1;
[0036] Figure 3 An optical photograph of the interface of the nano-slurry prepared in Example 1 after sintering at 180°C;
[0037] Figure 4 An optical photograph of the interface of the nano-slurry prepared in Example 1 after sintering at 190°C;
[0038] Figure 5 SEM image of the alloy nanoparticles prepared in Comparative Example 1.
[0039] Figure 6 The XRD pattern of the alloy nanoparticles prepared in Comparative Example 1 is shown. Detailed Implementation
[0040] To make the above-mentioned objects, features and advantages of the present invention more apparent and understandable, the specific embodiments of the present invention will be described in detail below with reference to the examples in the specification.
[0041] Many specific details are set forth in the following description in order to provide a full understanding of the invention. However, the invention may also be practiced in other ways different from those described herein, and those skilled in the art can make similar extensions without departing from the spirit of the invention. Therefore, the invention is not limited to the specific embodiments disclosed below.
[0042] Secondly, the term "one embodiment" or "embodiment" as used herein refers to a specific feature, structure, or characteristic that may be included in at least one implementation of the present invention. The phrase "in one embodiment" appearing in different places in this specification does not necessarily refer to the same embodiment, nor is it a single or selective embodiment that is mutually exclusive with other embodiments.
[0043] Unless otherwise specified, the experimental methods used in the following examples are conventional methods. Unless otherwise specified, all materials, reagents, methods, and instruments used are conventional materials, reagents, methods, and instruments in the art, and can be obtained commercially by those skilled in the art. Furthermore, all solid and liquid reagents used are of analytical grade.
[0044] Example 1
[0045] (1) The method for preparing supersaturated silver-bismuth alloy nanoparticles in this embodiment is carried out according to the following steps:
[0046] Step 1: Silver metal salt AgNO3 and bismuth metal salt Bi(NO3)3 are added to the reaction vessel at a molar ratio of 20:1. β-Cyclodextrin is then added as an organic dispersant, with the total molar ratio of metal salt to organic dispersant in the precursors being 5:1. A mixed solution of ethylene glycol and diethylene glycol is then added, with a total molar concentration of metal salts of 0.2 mol / L and a volume ratio of ethylene glycol to diethylene glycol of 1:1. The mixture is stirred thoroughly at a speed of 200 rpm for 20 minutes.
[0047] Step 2: After the precursor solution is mixed evenly, use 20 mL of 99% pure hydrazine hydrate as a reducing agent, place it in a syringe, and quickly inject the reducing agent into the precursor solution in a short time while stirring at a speed of 400 r / min.
[0048] Step 3: After the reaction is complete, the obtained reactants are centrifuged at 4000 r / min for 15 min to remove the supernatant and obtain the precipitate. The precipitate is then washed with acetone, deionized water and ethanol alternately three times to obtain single-phase supersaturated silver-bismuth alloy nanoparticles.
[0049] The supersaturated silver-bismuth alloy nanoparticles obtained above were characterized, and the TEM characterization results are as follows: Figure 1 As shown, by Figure 1 It can be seen that the obtained particles are nanoscale particles, and bismuth is uniformly mixed in the silver metal lattice, forming supersaturated silver-bismuth alloy nanoparticles. The XRD characterization results are as follows: Figure 2 ,Depend on Figure 2 It can be seen that the obtained particles only have silver metal lattice peaks and no bismuth metal lattice peaks, indicating that a single-phase supersaturated silver-bismuth alloy has been prepared.
[0050] (2) The method for preparing sintering slurry using the supersaturated silver-bismuth alloy nanoparticles prepared above shall be carried out according to the following steps:
[0051] Step 1: Mix 0.7g of supersaturated nano-silver bismuth alloy nanoparticles, 0.1g of polyethylene glycol, 0.5g of ethanol, 0.5g of terpineol, 0.1g of stearic acid and 0.1g of rosin resin to obtain a solid-liquid mixture.
[0052] Step 2: Use a slurry mixer to thoroughly mix the above mixture, let it stand to evaporate the ethanol, and prepare a sintering slurry.
[0053] The sintering paste obtained above was screen-printed onto the substrate pads, and sintered at 180°C and a sintering pressure of 5 MPa for 60 minutes to obtain the sintered interface as shown. Figure 3 As shown, by Figure 3 It can be seen that the nano-slurry and the copper pad have good inter-interface, forming a tight metallurgical connection. The low porosity inside the sintered body indicates that the solder joint has good performance.
[0054] The sintering paste obtained above was screen-printed onto the substrate pads, and sintered at 190°C and a sintering pressure of 5 MPa for 60 minutes to obtain the sintered interface as shown. Figure 4 As shown, by Figure 4 It can be seen that the nano-slurry and the copper pad have good inter-interface, forming a tight metallurgical connection. The porosity inside the sintered body is further reduced, indicating that the solder joint performance is better than that at 180℃.
[0055] Example 2
[0056] The difference between this embodiment and Embodiment 1 is that the molar ratio of silver metal salt AgNO3 to bismuth metal salt Bi(NO3)3 is 3:1, while the remaining process steps and parameter settings are the same as in Embodiment 1.
[0057] Comparative Example 1
[0058] The difference between this comparative example and Example 1 is that the solvent is deionized water, while the remaining process steps and parameter settings are the same as in Example 1.
[0059] The microstructure of the alloy nanoparticles obtained in this comparative example was characterized, and the results are as follows: Figure 5 As shown, by Figure 5 It can be seen that the obtained alloy nanoparticles are nanoscale particles. Further analysis of their XRD patterns reveals... Figure 6It is known that the alloy nanoparticles contain not only silver but also Bi and bismuth oxide. This is because bismuth salts, which provide bismuth, are difficult to dissolve in large quantities in water. Furthermore, the significant difference in chemical potential between silver and bismuth ions in aqueous solution leads to a difference in reaction rates, making it difficult for the two metals to react simultaneously. The nanoparticles of silver and bismuth are synthesized and precipitated in solution in two steps. Due to the reactive nature of bismuth, the nanoparticles of bismuth are easily oxidized during the preparation process and in air, forming bismuth oxide structures. Therefore, it is impossible to stably synthesize supersaturated nanoparticles. These nanoparticles lack sintering properties, and stable metallurgical bonding is difficult to achieve even at 250°C.
[0060] Although the present invention has been disclosed above with reference to preferred embodiments, it is not intended to limit the present invention. Anyone skilled in the art can make various modifications and alterations without departing from the spirit and scope of the present invention. Therefore, the scope of protection of the present invention should be determined by the claims.
Claims
1. A method for preparing supersaturated silver-bismuth solid solution nanoparticles, characterized in that, include: (1) Silver metal salt and bismuth metal salt are placed in a reaction vessel in proportion, organic dispersant and solvent are added, and the mixture is stirred until completely dissolved to obtain a precursor solution; (2) The precursor solution and the reducing agent solution were mixed and reacted under low temperature conditions to obtain silver bismuth solid solution nanoparticles; (1) The bismuth metal salt is one or more of bismuth nitrate, bismuth chloride, and bismuth oxide, and the molar content of the bismuth salt in the precursor solution is 0.0001~30% of the total molar content of the metal salt; (2) The reducing agent is one or more of hydrazine hydrate, sodium borohydride, potassium borohydride, sodium hypophosphite, polyol, and ascorbic acid, and the reaction temperature is -50~50℃ under low temperature conditions. The molar content of bismuth in silver-bismuth solid solution nanoparticles is 0.0001~30%. The nano-slurry prepared from silver-bismuth solid solution nanoparticles has a weld shear strength of 12~40MPa and a thermal conductivity of 100~300W / (m·K) after sintering.
2. The preparation method according to claim 1, characterized in that, (1) The silver metal salt is one or more of silver nitrate, silver sulfate, silver oxalate, silver chloride, silver bromide, and silver iodide; the organic dispersant is one or more of citric acid, sodium citrate, polyvinylpyrrolidone, octadecylamine, hexadecyltrimethylammonium bromide, sodium dodecylbenzenesulfonate, and dodecyl mercaptan; the solvent is one or more of ethanol, acetone, ethylene glycol, ethyl acetate, dichloromethane, methyl chloride, dimethylformamide, ethylene glycol ether, 1,2-ethylene glycol, and ethylene glycol butyl ether, or water and one or more of ethanol, acetone, ethylene glycol, ethyl acetate, dichloromethane, methyl chloride, dimethylformamide, ethylene glycol ether, 1,2-ethylene glycol, and ethylene glycol butyl ether.
3. The preparation method according to claim 1, characterized in that, (1) The total concentration of silver and bismuth metal salts in the precursor solution is 0.01~10 mol / L; the concentration of organic dispersant is 0.1~10 g / L.
4. The preparation method according to claim 1, characterized in that, (2) The reducing agent concentration in the reducing agent solution is 0.1~10 mol / L, and the total molar ratio of the added reducing agent to the metal salt in the precursor solution is (1~5):
1.
5. The preparation method according to claim 1, characterized in that, (2) The reaction time under medium and low temperature conditions is 2~60 min, and the stirring speed is 200~2000 r / min.
6. A supersaturated silver-bismuth solid solution nanoparticle prepared by the method according to any one of claims 1 to 5, characterized in that, The nanoparticles have a diameter of 5~500nm.
7. A sintering slurry, characterized in that, The sintering slurry is composed of supersaturated silver-bismuth solid solution nanoparticles as described in claim 6, an organic solution, a dispersant, a flux, and a binder in a mass percentage ratio of 50-90%: 5-45%: 0.01-5%: 0.01-5%: 0.01-5%, and the solid content of the sintering slurry is above 80%.
8. The sintering slurry according to claim 7, characterized in that, The organic solvent is one or more of ethanol, ethylene glycol, diethylene glycol, triethylene glycol, terpineol, polyethylene glycol, glycerol, and ethyl acetate; the dispersant is one or more of citric acid, sodium citrate, β-cyclodextrin, octadecylamine, hexadecyltrimethylammonium bromide, sodium dodecylbenzenesulfonate, and dodecyl mercaptan; the flux is rosin resin or a rosin resin derivative; and the binder is one or more of stearic acid, fish oil, polyethylene terephthalate, and epoxy resin.
9. A low-temperature sintering method for the sintering slurry according to claim 7 or 8, characterized in that, The sintering paste is screen-printed onto the substrate pads, the chip is aligned and placed, and hot-pressed at a temperature above 180°C for 5 to 200 minutes under a sintering pressure of 0 to 30 MPa.
Citation Information
Patent Citations
KR20210101848A